German car buyers' willingness to pay to reduce CO2 emissions - Martin Achtnicht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Motorised individual transport strongly contributes to global CO2 emissions, due to its intensive usage of fossil fuels. Current political efforts addressing this issue (i.e. emission performance standards in the EU) are directed towards car manufacturers. This paper focuses on the demand side. It examines whether CO2 emissions per kilometre is a relevant attribute in car choices. Based on a stated preference experiment among potential car buyers from Germany, different mixed logit specifications are estimated. In addition, distributions of willingness to pay measures for an abatement of CO2 emissions are obtained. The results suggest that the emissions performance of a car matters substantially, but its consideration varies heavily across the sampled population. In particular, some evidence on gender, age and education effects on climate concerns is provided.
Keywords: C25; D12; Q51; 330; CO2 emissions; Willingness to pay; Passenger cars; Stated preferences; Mixed logit; Personenkraftwagen; Motorisierter Individualverkehr; Verkehrsökologie; Klimaschutz; Willingness to pay; Luftreinhaltung; Deutschland